2021
DOI: 10.1186/s12888-021-03068-7
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders among seasonal migrant farmworkers in Northwest Ethiopia

Abstract: Background Seasonal migrant farmworkers in Ethiopia are a vulnerable segment of the population facing numerous threats to their mental health. This research aimed to determine the magnitude of common mental disorders (CMDs) and its associated factors among seasonal migrant farmworkers in the northwest of Ethiopia. Methods A cross-sectional study was conducted. A total of 950 seasonal migrant farmworkers were selected randomly. CMDs were assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…This happens because many farmers have temporary contracts or do not have formal contracts 29. Similar results have been found across seasonal farmers in Ethiopia, where a higher prevalence of common mental disorders was reported 30…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This happens because many farmers have temporary contracts or do not have formal contracts 29. Similar results have been found across seasonal farmers in Ethiopia, where a higher prevalence of common mental disorders was reported 30…”
Section: Discussionsupporting
confidence: 87%
“…29 Similar results have been found across seasonal farmers in Ethiopia, where a higher prevalence of common mental disorders was reported . 30 In our study, symptoms of mental disorders increased with additional hours of excessive work. This finding is consistent with the North American study reported by Kearney et al, where 60% of farmers who worked >40 hours per week reported being very stressed.…”
Section: Open Accesssupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, low agricultural incomes, and high income volatility aggravates the already poor mental health of agrarian workers. Among many, financial burden and farm losses have been one of the crucial predictors of poor mental health and cases of suicide among the agrarian workforce [18,[20][21][22][23][24][25][26][27][28][29][30]. Therefore, we hypothesize that insurance can have a significant role in providing adequate protection to agricultural workers in adverse income situations, which can subsequently prevent development of mental illness or further deterioration of mental health conditions of the agrarian workers.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Because of the hard work done under difficult conditions, farming is considered as physical and mental health hazards. [4] Work-related disorders refer to problems that are also known as cumulative trauma disorder, repetitive strain injury, or overuse syndromes. [5] Agriculture workers are the agricultural sector's most important pillars of growth and development.…”
Section: Introductionmentioning
confidence: 99%